Literature Review on the Ethnobotany, Phytochemistry, Pharmacological, Molecular Docking Study of Vitex madiensis Oliv. (Lamiaceae) and New Research Perspectives - Moke Lengbiye, Emmanuel; Koto-Te-Nyiwa Ngbolua, Jean-Paul; Bekomo, Jeef Iteku; Tshibangu, Damien Sha-Tshibey; Mbing, Joséphine Ngo; Pegnyemb, Dieudonné Emmanuel; Mpiana, Pius Tshimankinda (Orapuh Journal, 2025)
IntroductionVitex madiensis (Lamiaceae) is a medicinal plant widely utilized in traditional African medicine for its antimicrobial, anti-inflammatory, and hepatoprotective properties. Its rich phytochemical diversity, including flavonoids, terpenoids, and iridoids, has garnered attention for its potential in combating antimicrobial resistance, particularly against β-lactamase-producing bacteria, which are major contributors to global antibiotic resistance.PurposeThis study aims to review the ethnobotanical, phytochemical, and pharmacological properties of Vitex madiensis, evaluate the molecular docking potential of its bioactive compounds against β-lactamase (PDB ID: 1fco), and assess their pharmacokinetic and toxicological profiles to explore their viability as antimicrobial agents.MethodsA total of 60 chemical compounds from Vitex madiensis and related Vitex species were analyzed. Molecular docking was performed using AutoDock Vina to evaluate interactions with β-lactamase, with gentamicin serving as the reference molecule. Pharmacokinetic and toxicological analyses were conducted on 54 compounds to predict drug-likeness, toxicity, and interaction profiles.ResultsMolecular docking revealed nine compounds with significant interactions. Among them, 3-epi-maslinic acid demonstrated the highest binding affinity (-8.8 kcal/mol), outperforming gentamicin (-8.3 kcal/mol). Other compounds, including kaempferol, luteolin, and vitetrifolin C, exhibited promising affinities (-7.9 to -8.2 kcal/mol). Pharmacokinetic analysis indicated that most compounds were non-toxic, with 8-epi-sclareol, citronellyl acetate, rotundifaran, vitexifolin E, and vitexifolin C exhibiting optimal drug-like properties. However, caution is warranted due to potential drug interactions observed in certain compounds.ConclusionThis review highlights the therapeutic potential of Vitex madiensis as a cost-effective and accessible source for antimicrobial drug development, particularly against β-lactamase-producing bacteria. The integration of molecular docking with pharmacokinetic predictions provides novel insights into the synergistic potential of its bioactive compounds. Future research should further explore these findings through in vitro and in vivo studies.